1980
DOI: 10.1002/pol.1980.170181108
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of morphology of composite polymer emulsion particles by the soap titration method

Abstract: The occupied area (Am) of a sodium dodecyl benzene sulfonate molecule adsorbed on particles was measured by the soap titration method. The Am values are 214, 133, and 53 Å2 for poly(methyl acrylate) (I), poly(methyl methacrylate) (II), and polystyrene (III), respectively. For methyl metharylate‐styrene copolymer emulsions the additivity was established between the Am value and copolymer composition. Composite emulsion particles consisting of I/II, I/III, and II/III were prepared by seeded emulsion polymerizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(85 citation statements)
references
References 10 publications
3
81
0
1
Order By: Relevance
“…The stronger adsorption is related to a lower value of the area covered by a molecule of emulsifier (parking area), and it is well known that the parking area decreases with the hydrophobicity of the organic phase. 11 This is confirmed by the results presented in Table 2, which showed that, for a given concentration of emulsifier, the surface tension of the miniemulsion increased with alkyd resin contents even though the total surface area of the droplets decreased. However, the droplet sizes reported were those corresponding to a high number of cycles in the homogenizer, i.e., when no further reduction of the droplet size was observed.…”
Section: Resultssupporting
confidence: 90%
“…The stronger adsorption is related to a lower value of the area covered by a molecule of emulsifier (parking area), and it is well known that the parking area decreases with the hydrophobicity of the organic phase. 11 This is confirmed by the results presented in Table 2, which showed that, for a given concentration of emulsifier, the surface tension of the miniemulsion increased with alkyd resin contents even though the total surface area of the droplets decreased. However, the droplet sizes reported were those corresponding to a high number of cycles in the homogenizer, i.e., when no further reduction of the droplet size was observed.…”
Section: Resultssupporting
confidence: 90%
“…To prepare structured latex particles, three main methods of preparation have been considered and studied: First, the functionalization of latexes by copolymerization of a monomer with the addition of small amounts of a second monomer bearing a chemically reactive group such as carboxyl, [1][2][3][4] amide, 5,6 sulfate, 7,8 sulfonate, 9 and hydroxyl; 10,11 second, the copolymerization of comonomers that markedly differ in their water solubility 12,13 or reactivity ratios; 14,15 and third, the polymerization in the presence of a polymer dispersion that is prepared in advance; that is, seeded emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using PMMA seed particles and styrene as the added monomer have been reported 5,[7][8][9][10] but none of these studies examined partially polymerized host particles, in which monomer from the host polymer remains when the addition of the second monomer commences. The characteristics of our process differ markedly from those used in previous studies.…”
Section: Mma/sty Composite Particlesmentioning
confidence: 99%